2011
DOI: 10.1111/j.1365-2702.2010.03602.x
|View full text |Cite
|
Sign up to set email alerts
|

Is anybody listening? A qualitative study of nurses’ reflections on practice

Abstract: Research demonstrates that a well-qualified, stable nursing workforce improves quality of health care and health outcomes. Changing the work environment and fostering a positive workplace culture seems fundamental to supporting the retention of nurses, that this is not occurring in some areas in the current climate is a concern for the profession and those responsible for the provision of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 34 publications
9
54
0
Order By: Relevance
“…Nurses (and midwives) accounts, however, are far from this ideal. From a colleague's perspective, nurses fail to support one another . This can include the newly graduated nurse transitioning into their first nursing/midwifery position (and hoping not to be ‘thrown to the wolves’).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses (and midwives) accounts, however, are far from this ideal. From a colleague's perspective, nurses fail to support one another . This can include the newly graduated nurse transitioning into their first nursing/midwifery position (and hoping not to be ‘thrown to the wolves’).…”
Section: Discussionmentioning
confidence: 99%
“…Workload may become a stressor in situations which require high effort to sustain an expected performance level, consequently eliciting negative responses, including burnout (Hasselhorn et al., ; Schaufeli, Bakker, & Van Rhenen, ). High workloads frequently have an adverse effect on nursing retention in the organization (Hayes et al., ; Huntington et al., ) and in the profession (Bakker & Sanz‐Vergel, ; Hasselhorn et al., ), so we expect that:
H2: Greater workload is positively related to intention to leave the organization/profession through a positive relationship with burnout.
…”
Section: The Studymentioning
confidence: 99%
“…Data here were drawn from the Australian and New Zealand Nurses and Midwifes e-Cohort study (N = 3,968), a self-reported survey of practicing nurses and midwives across multiple working environments (Huntington et al, 2011;Tuckett et al, 2009). The e-cohort data set contains longitudinal, population-based information, making possible the examination of factors associated with the nurse and midwife workforce and health outcomes.…”
Section: Settingmentioning
confidence: 99%